Titanium isopropoxide-mediated cis-selective synthesis of 3, 4-substituted butyrolactones from CO2. Issue 18 (14th February 2022) - Sahari, Aleksi; Do, Cuong Dat; Mannisto, Jere K.; Antico, Emanuele; Amaratunga, Angelo; Hopmann, Kathrin H.; Repo, Timo
Abstract : Titanium-mediated 1, 2-activation of Grignard reagents enables α and β insertion of carbon dioxide and arylaldehyde to prepare cis -3, 4 butyrolactones. Abstract : We report a Ti(OiPr)4 -mediated multicomponent reaction, which produces 3, 4-substituted cis -δ-lactones from alkyl magnesium chloride, benzaldehyde and CO2 . The key intermediate, titanacyclopropane, is formed in situ from Ti(OiPr)4 and a Grignard reagent, which enables 1, 2-dinucleophilic reactivity that is used to insert carbon dioxide and an aldehyde. An alternative reaction route is also described where a primary alkene is used to create the titanacyclopropane. A computational analysis of the elementary steps shows that the carbon dioxide and the aldehyde insertion proceeds through an inner-sphere mechanism. A variety of cis -butyrolactones can be synthesized with up to 7 : 1 diastereoselectivity and 77% yield.